2012
DOI: 10.1590/s1020-49892012000900005
|View full text |Cite
|
Sign up to set email alerts
|

Mortalidade cardiovascular e impacto de técnicas corretivas de subnotificações e óbitos mal definidos

Abstract: This correction made it possible to identify an excess of deaths that had not been computed, generating more reliable adjusted and corrected death rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The coverage quality of information systems has an important role in health surveillance, especially in monitoring mortality. However, the information quality of death registries in Brazil, in addition to regional disparities in access to health services, can lead to underestimated mortality rates, even with improved coverage over the years [ 28 ],[ 29 ],[ 44 ]. Thus, in this study, we corrected the number of deaths due to CD according to the records of ill-defined death causes while, ignoring age and sex, resulting in a 27% increase in CD as a basic cause of death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The coverage quality of information systems has an important role in health surveillance, especially in monitoring mortality. However, the information quality of death registries in Brazil, in addition to regional disparities in access to health services, can lead to underestimated mortality rates, even with improved coverage over the years [ 28 ],[ 29 ],[ 44 ]. Thus, in this study, we corrected the number of deaths due to CD according to the records of ill-defined death causes while, ignoring age and sex, resulting in a 27% increase in CD as a basic cause of death.…”
Section: Discussionmentioning
confidence: 99%
“…The correction process was used because of the great disparity in information quality among the Brazilian geographic regions, and because during the period under study, there were important improvements in death registry quality in Brazil due to the expansion of health services with the implementation of the Unified Health System (SUS) [ 28 ]. In addition, Holford (1991) affirms that improvements in death certificates may have a period effect and so, in order not to draw erroneous conclusions regarding the evolution Chagas disease mortality, we have chosen to correct death records [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…, 17 , 18 However, there was a relatively significant proportion of these causes among IDCD (9.3% of the reclassified IDCD for Brazil in 2010), probably related to the active search for clarifying IDCD that was conducted in the IML in various municipalities. Studies in Brazilian municipalities also showed significant proportions of external causes among IDCD 1 …”
Section: Discussionmentioning
confidence: 99%
“…We made some corrections due to the poor quality of the information obtained from the Information System on Mortality (SIM) and then we progressed in three steps: (1) proportional redistribution of the classified registers with age and/or sex that we ignored, (2) redistribution of the classified deaths as causes that were poorly defined amongst the known causes 13 , with the exception of the external causes, and (3) correction of the sub-register of deaths for each of the geographical regions and sexes in accordance with the description that follows.…”
Section: Methodsmentioning
confidence: 99%